1972
DOI: 10.1002/1097-0142(197210)30:4<885::aid-cncr2820300404>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Increased immunogenicity of ehrlich ascites cells after heat treatment

Abstract: Immunization of Swiss mice with Ehrlich ascites cells which had been exposed in vitro to 42.C for 3 hours is more effective, so far as subsequent tumor transplantation is concerned, than immunization with radiation‐inactivated cells or with cells exposed to 42.5C for 6 hours. These results, which indicate that upon moderate heat treatment there is a definite increase of the immunogencity of these cells, may have some relevance as to the mechanism of the delayed tumor regression which is often clinically observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Another important biologic effect of HT is the capacity to enhance the antigenic presentation to effector cells, and the production of heat shock proteins (hsp) [90][91][92][93]. Furthermore, HT recruits into the tumor area neutrophils, macrophages, natural killer cells, myeloid suppressor cells and regulatory T cells [92][93][94].…”
Section: • Mitochondria Suffer Different Alterations In Their Cristaementioning
confidence: 99%
“…Another important biologic effect of HT is the capacity to enhance the antigenic presentation to effector cells, and the production of heat shock proteins (hsp) [90][91][92][93]. Furthermore, HT recruits into the tumor area neutrophils, macrophages, natural killer cells, myeloid suppressor cells and regulatory T cells [92][93][94].…”
Section: • Mitochondria Suffer Different Alterations In Their Cristaementioning
confidence: 99%
“…Hyperthermia may modify tumor antigens to produce a host immune response [156]. This immune response may be one mechanism involved in progressive tissue injury after focal hyperthermia application and potentially influence patterns of tumor recurrences [143,177]. The effect of immunity on tissue destruction following focal hyperthermia largely depends on the antigenicity of cells in the experimental design.…”
Section: Immune Responsementioning
confidence: 99%
“…6,7 The hyperthermic effect of MCLs was examined in an in vivo study, and complete tumor regression was observed. 8 Since some researchers have reported that heat treatment itself can enhance the immunogenicity of cancer cells, [9][10][11][12] we previously investigated hyperthermia-induced antitumor immunity in T-9 rat glioma cells in vivo. 13 This induced immunity continued for an extended period of time, and the rats treated with hyperthermia completely rejected T-9 cells as a metastasis model.…”
mentioning
confidence: 99%